Determinants of e-government implementation at the local level: an empirical model - Dias, Gonçalo Paiva (2020)
Purpose: The empirical research of e-government at the local level has been the subject of many studies in the last two decades. The evidence collected by those studies constitutes a relevant opportunity towards the development of a theory of local e-government implementation. However, several synthesis efforts are needed before such a theory can be developed. This article contributes to that endeavour by proposing an empirical model of the determinants of e-government implementation by local governments. Methodology: The empirical model results from the systematic revision of 59 primary studies published in scientific journals, between 2002 and 2018. As a starting point, a conceptual map relating concepts such as readiness, diffusion, adoption, implementation, and institutionalization is presented. Findings: There is a common set of determinants that explains local e-government implementation in general, and three other sets of determinants that contribute to differentiate each one of three e-government dimensions: e-participation, e-transparency, and e-services. Research implications: Because it was found that different determinants are associated with different e-government dimensions, future empirical studies should differentiate between those dimensions when studying local government. Originality: This is the first study to attempt a synthesis effort on the determinants of e-government implementation by local governments.